IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI DESA DOLODUO SATU KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MOGONDOW - Bakir Bonde; Agus Wahono (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This research describes the implementation process of Village Fund Allocation Policy (ADD) and Village Fund (DD) as seen from the indicators of organizing, interpretation and application as well as the factors that support and influence the implementation of ADD and DD Policy in Mopuya Village, Dumoga District North Bolaang Mongondow District. This study used descriptive qualitative method. Qualitative methods interpret the meaning of an event of interaction behavior of people in certain situations from their own perspective. The results show that the implementation process of ADD and DD Policy in Mopuya Village, North Dumoga District has not fully lead to the socio-economic development of rural people. Factors influencing successful implementation of ADD and DD programs in the empowerment of rural communities such as Human Resources (HR), socialization and channeling of funds, and coordination is still not in accordance with expectations that led to the implementation of programs ADD and DD in Mopuya Village District Dumoga Utara District Bolaang Mongondow does not run optimally. Keywords: policy implementation, village funds, village communities